Juridical Analysis of Interfaith Marriage in Indonesian Positive Law Perspective - Rully Affan Pamungkas; Rastra Wahyudityana; Fadlan Fadlan (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2025)
This research conducts a comprehensive juridical analysis of interfaith marriage within the framework of Indonesian positive law, examining the legal complexities and regulatory challenges in the current legal system. The study critically analyzes the existing legal instruments, including Marriage Law No. 1 of 1974, compilation of Islamic Law, and relevant Supreme Court decisions that govern interfaith marriages in Indonesia. Through doctrinal legal research methodology, this study investigates the legal vacuum surrounding interfaith marriages and its implications on citizens' constitutional rights. The research examines how different legal interpretations by civil registry offices, religious courts, and other legal institutions affect the implementation of interfaith marriage regulations. Findings indicate substantial inconsistencies in legal interpretation and application, leading to legal uncertainty for couples seeking interfaith marriages. The study reveals that while Indonesian positive law does not explicitly prohibit interfaith marriages, the absence of clear regulatory frameworks often results in practical obstacles and varying administrative practices across different regions. The research also explores how judicial decisions have shaped the legal landscape of interfaith marriages, analyzing landmark cases that have influenced current legal practices. This study concludes that there is an urgent need for legal reform to provide clear guidelines for interfaith marriages that align with constitutional principles while respecting religious values and human rights in Indonesia's pluralistic society.